1982
DOI: 10.1159/000117899
|View full text |Cite
|
Sign up to set email alerts
|

Mécanisme d’échange de la tyrosine entre le plasma et les érythrocytes chez le sujet normal et des patients psychiatriques

Abstract: The saturable mechanism of tyrosine (TYR) uptake by the membrane of red blood cells incubated at 37 °C has been studied in normal subjects and psychiatric patients. This uptake is markedly inhibited by incubation at 0 °C, and weakly inhibited by iodoacetic acid and ouabain. The uptake of TYR is significantly lower in unipolar- and bipolar-depressed patients, and significantly higher in schizophrenics compared to normal controls. These results indicate a possible disturbance of functional capacity of membrane t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

1984
1984
1990
1990

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 13 publications
2
7
0
Order By: Relevance
“…In a previous paper, we described a deficit of TYR transport in vitro by these cells from psychiatric patients [Widmer et al, 1982]. This finding has been confirmed by more recent studies .…”
Section: Introductionsupporting
confidence: 80%
See 3 more Smart Citations
“…In a previous paper, we described a deficit of TYR transport in vitro by these cells from psychiatric patients [Widmer et al, 1982]. This finding has been confirmed by more recent studies .…”
Section: Introductionsupporting
confidence: 80%
“…The decrease of specific TYR transport, observed only after sanguinarine, could be compared with the action of ouabain, as shown in a previous study, and suggests a small contribution of the active sodium move ment on this amino acid transport [Widmer et al, 1982], We used this alkaloid because it seems to be more potent on the (Na+, K+) ATPase than classical cardiotonics but with no binding to the ouabain receptors [Cala et al, 1982],…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…In previous observations, Tissot et al [1978] showed that monoamine precursors (L-tyrosine and L-tryptophan) exhibit modifications of their erythrocyte mem brane transports and plasma levels in depressed patients compared to controls Pringuey et al, 1986;Widmer et al, 1982]. Further, clinical improve ment correlates with normalization of these biochemical parameters [Bovier et al, 1988], Plasma red cell trans ports of tyrosine and tryptophan were then hypothesized to be valuable biological markers in affective disorders: abnormalities in the function of brain neurotransmitters could be implicated in their etiology.…”
Section: Introductionmentioning
confidence: 97%